Transition and nostalgia: the Acandí people nourishing system, Colombia - Gloria Margarita Alcaraz; Fanny Cecilia Pérez T (Revista Facultad Nacional de Salud Pública, 2007)
Objective: to know and understand the nourishing system of the Acandí people relative to their economic and social history, providing elements for intercultural health care. Methodology: ethnography focused in the nourishing system. A total of 33 semi–structured interviews were performed, three focal groups were organized and ﬁeld study was carried on. Manual analysis was performed. Results: looking back into the past one can realize how planting, harvesting, hunting, ﬁshing, community sharing of foods (were daily socialization occurs) recede today in front of media, tourism, unrest, and changing methods of production. Present day economic problems force people to pass from three daily meals to only two, affecting specially elders and children. Conclusions: despite nourishing transition, nourishing identity remains with nostalgia of better by-gone times and present day evidence of serious nourishing shortcomings. It is then convenient to establish polices and clear and responsible planning to preserve nourishing culture, nourishing security and the empowerment of the Acandí people in relation to those goals.